Pengaruh Pembelajaran Kooperatif Tipe Stad terhadap Hasil Belajar Matematika Siswa Kelas VIII SMPN 4 Selaru - Harry Henry Masrikat; Sylvia J.A. Sumarauw; Ontang Manurung; Navel Oktaviandy Mangelep (Departement of Mathematics Education, 2023)
The mathematics learning outcomes of SMPN 4 Selaru students are still very low, because students are less active in the learning process so that the mastery presentation is only 37%. An alternative to overcome this problem is to use STAD type cooperative learning. The purpose of this study was to find out whether the average mathematics learning outcomes of students who were taught using STAD type cooperative learning were more than the average mathematics learning outcomes of students taught without using STAD type cooperative learning. This type of research is quasi-experimental with a quantitative approach. Data analysis used is descriptive analysis, normality test, and homogeneity test. The instrument in this study was a test. The research subjects were 30 students of SMPN 4 Selaru. The results showed that the average student learning outcomes in the experimental class was 41.8 and the control class was 31.4. So it can be concluded that the average mathematics learning outcomes of students who are taught using STAD type cooperative learning is more than the average mathematics learning outcomes of students taught without using STAD type cooperative learning.